2014
DOI: 10.5326/jaaha-ms-5990
|View full text |Cite
|
Sign up to set email alerts
|

Upper Thoracic Disc Disease (T1–T9) in Large-Breed Dogs

Abstract: The purpose of this study was to identify large-breed dogs with intervertebral disc disease (IVDD) in the upper thoracic region (thoracic vertebrae 1-9 [T1-T9]). Medical records of all dogs that were diagnosed with IVDD on MRI between February 2008 and September 2011 were reviewed. Of 723 dogs diagnosed with IVDD based on MRI, 527 (72.9%) were small-breed dogs. There were 21 (10.7%) large-breed dogs with IVDD in the T1-T9 region, whereas no small-breed dogs were identified with lesions in that region. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
3
5
1
1
Order By: Relevance
“…The presence of multiple protrusions found in 58% of dogs with IVD protrusion in the present study was reported in another study, mainly in the thoracic region of German Shepherd dogs, and interestingly, the authors concluded that in the majority of the dogs the site of compression did not coincide with the site of neurological localization (Gaitero et al 2013). In another study with 723 dogs with IVD degeneration diagnosed by MRI, large-breed dogs were more likely to have multiple regions affected mainly in the T1-T9 region (Hearon et al 2014). The management of multiple protrusions is challenging, and it is a concern if all protrusions play a role in the development of clinical signs.…”
Section: Discussionsupporting
confidence: 72%
“…The presence of multiple protrusions found in 58% of dogs with IVD protrusion in the present study was reported in another study, mainly in the thoracic region of German Shepherd dogs, and interestingly, the authors concluded that in the majority of the dogs the site of compression did not coincide with the site of neurological localization (Gaitero et al 2013). In another study with 723 dogs with IVD degeneration diagnosed by MRI, large-breed dogs were more likely to have multiple regions affected mainly in the T1-T9 region (Hearon et al 2014). The management of multiple protrusions is challenging, and it is a concern if all protrusions play a role in the development of clinical signs.…”
Section: Discussionsupporting
confidence: 72%
“…Gründe für die Disposition der Rassen in Bezug auf die Lokalisation von BSV könnten anatomische wie biochemische Unterschiede zwischen den Rassen sein, doch liegen bislang keine wissenschaftlichen Erklärungsansätze vor. Das Fehlen eines Zusammenhangs von Körpergewicht und Alter zur Lokalisation des BSV in dieser Studie steht im Widerspruch zu den Ergebnissen von Hearon et al [15], die bei diesen Parametern eine deutliche Lokalisationsdisposition aufzeigten. Cherrone et al [9] und Tipold et al [33] stellten für BSV in der HWS fest, dass diese bei Hunden < 15 kg vermehrt im kranialen (C2/3) und bei Patienten ≥ 15 kg vermehrt im kaudalen (C6/7) Bereich der HWS lokalisiert waren.…”
Section: Gesamtsterblichkeitunclassified
“…With the described positioning and surgical approach, we were able to completely remove the compressive pathologic material, whether disc or tumor, in all but one patient. None of the cases experienced immediate post-operative deterioration, which has been a concern in many of the previous reports of cranial thoracic surgery in cats and dogs (Sumner and Simpson, 2007;Bottcher et al, 2008;Gaitero and Añor, 2009;Hearon et al, 2014). Hospitalization time was positively impacted by the lack of postoperative neurologic deterioration as well as lack of postoperative complications.…”
Section: Resultsmentioning
confidence: 85%
“…Compared with the reported surgical techniques to address cranial thoracic compressive spinal lesions in dogs and cats, one of the main advantages of the hemilaminectomy technique reviewed here includes a less extensive and invasive approach to the vertebrae, thus preserving the supporting ligaments, muscles, and bones such as ribs to maintain vertebral column stability (Parker, 1973;Liptak et al, 1999;Jäderlund et al, 2002;Gaitero and Añor, 2009;Hearon et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation